Telomerase Activation in Neoplastic Cell Immortalization and Tumour Progression - Looi, L.M.; Ng, M.H.; Cheah, P.L. (2007)
The unique ability of tumour cells to proliferate indefinitely is crucial to neoplastic progression as it allows these cells to express the aggressive properties of cancer without the censure of physiological ageing. This is in contrast to normal somatic cells which are subject to a “mitotic clock,” a phenomenon that has been linked to telomeric shortening after each round of cell replication, so that eventually the loss of genetic material reaches a critical stage and the cells undergo senescence and cell death. A study was conducted to investigate the role of telomerase, an RNA-containing enzyme that restores the telomere length, in the neoplastic cell immortalization and progression process. Fresh human tissue samples taken from excision specimens received by the Department of Pathology, University of Malaya Medical Centre, were investigated for telomerase activity using a commercial Telomerase PCR-ELISA kit (Boehringer Mannheim). Specimens comprised 33 breast lesions (10 infiltrating breast adenocarcinoma, 13 fibroadenoma and 10 non-neoplastic breast tissue), 27 colonic lesions (17 colonic adenocarcinoma and 10 non neoplastic colonic mucosa) and 42 cervical lesions (20 cervical carcinoma and 22 non neoplastic cervical tissues). Telomerase activity was found in 6 (60%) of 10 breast carcinomas, 6 (46%) of 13 fibroadenomas, none of the 10 nonneoplastic breast samples, 3 (17.6%) of 17 colon carcinomas and none of the 10 non-neoplastic colonic mucosal samples, 12 (60%) of 20 cervical carcinoma and 3 (13.6%) of 22 non-neoplastic cervical samples. 5/10 (50%) Stage I, 4/7 (57%) Stage II, 2/2 (100%) Stage III and 1/1 (100%) Stage IV cervical carcinomas showed telomerase activity. These findings support a contributory role for telomerase in tumourigenesis with activation occurring from neoplastic transformation and increasing with tumour progression.